Universal Maternal Health Coverage? Assessing the Readiness of Public Health Facilities to Provide Maternal Health Care in Indonesia - World Bank; Indonesia National Institute of Research and Development (World Bank, Jakarta, 2014)
Over the period 2011-2013, Indonesia had universal maternal health coverage for its population. Facility-based deliveries, however, remain relatively low: only about 63 percent of all deliveries occurred at a health facility in Indonesia. Recent progress notwithstanding, and despite the relatively high utilization rates for most key maternal health services, the level of maternal mortality remains high in Indonesia, especially in provinces such as West Papua, North Maluku, Papua, Gorontalo, West Sulawesi, Maluku, and South Kalimantan. This policy paper assesses the supply-side readiness of Indonesia s public health facilities in providing key maternal health services such as antenatal care (ANC) as well as basic and comprehensive emergency obstetric care. The focus in the paper is on assessing to what extent Indonesia's universal maternal health coverage is real. Ensuring the supply-side readiness of Indonesia's health system, incorporating lessons from the past experiences of implementing universal maternal health coverage under the different social health insurance programs, will be one key factor in ensuring that implementation of universal health coverage (UHC) results in improvements in health outcomes, including for maternal health. The policy paper is structured as follows: the section maternal health in Indonesia provides background on maternal health in Indonesia and on intended reforms to attain UHC by 2019. Assessing universal maternal health coverage in Indonesia provides information on maternal health benefits under existing social health insurance programs. Public facility supply-side service readiness for maternal health outlines the supply-side implications of maternal health coverage using national guidelines as well as the World Health Organization's (WHO's) service availability and readiness assessment (SARA) framework, focusing specifically on ANC as well as basic and emergency obstetric care services and presents an assessment of service readiness using facility-level data. The report concludes with policy implications in the final section, policy implications and conclusions.